Autoantibodies in psoriasis as predictors for loss of response and anti-infliximab antibody induction - Hoffmann, Jochen; Hartmann, Martin; Enk, Alexander; Hadaschik, Eva (British journal of dermatology, 2011)
Background Infliximab is successfully used to treat psoriasis and psoriatic arthritis. However, some patients lose therapeutic response after several cycles. Antibodies to infliximab (infliximab-Abs) are induced during treatment in a subgroup of patients and are thought to be associated with loss of response (LOR). Routine screening for infliximab-Abs is expensive and not regularly performed. A reliable and affordable method for identifying patients who are at risk for LOR to infliximab is desirable. Objectives To analyse the development of antinuclear antibodies (ANA)/antidouble-stranded DNA antibodies (anti-dsDNA) over time in patients with psoriasis receiving infliximab. To analyse if there is an association between ANA titres/anti-dsDNA concentrations, infliximab-Ab status and LOR. Methods A retrospective data analysis of 29 patients with psoriasis receiving infliximab was carried out. ANA titres and anti-dsDNA concentrations were regularly monitored in these patients and sera were tested for infliximab-Abs by enzyme-linked immunosorbent assay. Results Median ANA titres increased from 1 : 80 [interquartile range (IQR) 0 to 1 : 320, n = 29] pretreatment, to 1 : 1280 (IQR 1 : 640 to 1 : 1920, n = 15) after infusion 10, and 1 : 1920 (IQR 1 : 1280 to 1 : 2560, n = 10) after infusion 20. Infliximab-Abs were found in 21% of patients. Infliximab-Ab-positive patients and patients with LOR had significantly higher pretreatment anti-dsDNA concentrations and higher pretreatment ANA titres than infliximab-Ab-negative and responsive patients, respectively. Conclusions The results of this study suggest a role for autoantibodies in the identification of patients with psoriasis at higher risk of developing infliximab-Abs and of LOR under treatment with infliximab.
Gesehen am 29.07.2022